On application of Cramer’s rule - Apynis, Antanas (Lietuvos matematikos rinkinys, 2011)
The article analyses a possibility of modification of Cramer’s rule. The modified formulas for the solution of a system of linear equations, with application of which the volume of calculation reduces, are suggested.